Imprinting Pentaphyrin on Conductive Electropolymerized Dipyrromethane Films: A New Strategy towards the Synthesis of Photokilling Materials. Issue 4 (23rd March 2020) - Comuzzi, Clara; Fiorot, Andrea; Baggio, Anna; Maifreni, Michela; Strazzolini, Paolo; Marino, Marilena; Susmel, Sabina
Abstract: We report herein the synthesis and photoinduced bactericidal activity of two new polymeric materials, obtained by imprinting the photosensitizer 20‐(4‐carboxyphenyl)‐2, 13‐dimethyl‐3, 12‐diethyl‐[22]pentaphyrin (PCox, 1 ) into suitable electropolymerized dipyrromethane films. 5‐Phenyl‐dipyrromethane (5‐ph‐DP) and 5‐(4‐pyridyl)dipyrromethane (5‐py‐DP) have been selected as the monomers for the synthesis of the materials in order to assess the correlation between the substituent in C5 and the capability in Pcox uptake. Both films have been tested in their photokilling ability toward Staphylococcus aureus by using a multi‐LED blue lamp at a fluence rate of 40 W/m 2 . Poly‐5‐py‐DP/PCox, with a PCox load of 10 −8 mol/cm 2, achieved a 4‐log reduction in microbial viability after 60 min of irradiation. The polymeric films proved to be stable over time and under oxidation conditions; in addition, no loss of photosensitizer was observed during the experiments, thus demonstrating that the bactericidal action was effectively brought by the ROS generated by PCox immobilized in the material. After use, the films were recharged with PCox, with almost complete recovery of their photodynamic efficiency. Abstract : Active when trapped: Electropolymerization has been applied to imprint a photosensitizer into polydipyrromethane networks. The synthesized materials entrap the active molecule on a scale of nanomoles per square centimeter to produce singlet oxygen and a 4‐log reduction in the viability of S. Aureus after 60 min of irradiation. After use, the material can be reloaded with a new batch of photosensitizer, almost completely restoring its photokilling ability.